2006
DOI: 10.1107/s0909049506043111
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-embedded protein crystals

Abstract: Rapid vitrification followed by the replacement of the vitrified water by a solvent (freeze substitution) and then resin is a widely used procedure for preparing biological samples for electron microscopy. The resulting plasticembedded samples permit convenient room-temperature sectioning (microtomy) and can yield well preserved cellular structures. Here this procedure has been applied to crystalline protein samples, and it is shown that it is possible to freeze-substitute vitrified crystals while preserving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…One of these is in specimen preparation, and Ravelli et al (2007) describe first attempts to embed a protein crystal in plastic using techniques developed for electron microscopy samples.…”
mentioning
confidence: 99%
“…One of these is in specimen preparation, and Ravelli et al (2007) describe first attempts to embed a protein crystal in plastic using techniques developed for electron microscopy samples.…”
mentioning
confidence: 99%
“…These studies generally showed high resolution detail (up to ∼1 nm) in the uncut block, but much worse preservation in the subsequent sections, suggesting that cutting is a major source of damage [7–9]. Moreover, a recent X-ray diffraction study demonstrated reflections to better than 6 Å from crystals of lysozyme embedded in plastic, thus showing that embedded protein can be very well preserved and again consistent with the idea of damage due to cutting [10].…”
Section: Introductionmentioning
confidence: 84%
“…Whatever the process involved, having crystals that easily photoconvert from green to red in dried conditions could potentially be a great advantage in terms of robustness of the biological matter used as optical data storage media. Since there would be no need to maintain and control the humidity in the sample, we could even envisage preserving and embedding single crystals inside a plastic polymer matrix as it has been already shown to be possible (Ravelli et al, 2007).…”
Section: Multicolour 3d Data Storage Using Crystals Of Irisfpmentioning
confidence: 98%